The Type IX Secretion System and Its Role in Bacterial Function and Pathogenesis - Veith, P D; Glew, M D; Gorasia, D G; Cascales, E; Reynolds, E C (Journal of dental research, 2022)
, and species found in severe periodontitis use the Type IX Secretion System (T9SS) to load their outer membrane surface with an array of virulence factors. These virulence factors are then released on outer membrane vesicles (OMVs), which penetrate the host to dysregulate the immune response to establish a positive feedback loop of chronic, inflammatory destruction of the tooth's supporting tissues. In this review, we present the latest information on the molecular architecture of the T9SS and provide mechanistic insight into its role in secretion and attachment of cargo proteins to produce a virulence coat on cells and OMVs. The recent molecular structures of the T9SS motor comprising PorL and PorM as well as the secretion pore Sov, together with advances in the overall interactome, have provided insight into the possible mechanisms of secretion. We propose the presence of PorL/M motors arranged in a circle at the inner membrane with bent periplasmic rotors interacting with the PorN protein. At the outer membrane, we envisage a slide carousel model where the PorN protein is driven around a circular track composed of PorK. Cargo proteins are transported by PorN to PorW and the Sov translocon just as slides are rotated to the projection window. Secreted proteins are proposed to then be shuttled along highways consisting of the PorV shuttle protein to an array of attachment complexes distributed around the cell. The cell surface attachment of cargo is a hallmark of the T9SS, and in and , this attachment is achieved via covalent bonding to a linking sugar synthesized by the Wbp/Vim pathway. The cell-surface attached cargo are enriched on OMVs, which are then released from the cell.